Tantangan dan Inovasi Manajemen Bimbingan dan Konseling di Era Digital: Sebuah Kajian Literatur - Larasuci Arini; Neviyarni Neviyarni; Firman Firman (Badan Penerbit STIEPARI Press, 2025)
Digital transformation has changed the paradigm of guidance and counseling (BK) services in educational institutions. This study aims to identify challenges and summarize various innovations in BK service management in the digital era through a review of scientific literature. The method used is a literature review with a qualitative descriptive approach to relevant sources published between 2015 and 2024. The findings reveal that the main challenges in digital BK management include technological literacy gaps, infrastructure limitations, and ethical and data security issues related to clients. On the other hand, emerging innovations include the use of online platforms such as Zoom and Google Meet, integration of AI chatbots, e-supervision systems, and the utilization of social media and mobile-based counseling applications. This study emphasizes the need to enhance counselors' digital competencies, strengthen ethical regulations, and provide institutional policy support to ensure the sustainability and relevance of digital BK services in the future.